A Morbid, Finite Bond: Derrida, Freud and Archival Technologies of Inscription - Switzer, Adrian (Bollettino Filosofico, 2021)
Focusing on two of Derrida’s works on Freud – Freud and the Scene of Writing (1967) and Archive Fever (1994) – the article first traces the literalization of figures of writing from the early to late work. Specifically, the article reads Archive Fever as the realization of the theme of the materialization of writing technologies first introduced in the 1967 essay. By tracing the tendency of technological figures of writing to converge what is singular and what is repeatable in analogical relations, the article identifies the singularity of such relations with their materialization in writing technologies. Such technological and material singularity, the article concludes, provides Derrida with a model of (un)natural relation between deconstruction and psychoanalysis – with the struck-through “un” a sign of the «right on [à même]» of technologized, material writing. The morbid, finite bond that Derrida forges between deconstruction and psychoanalysis, then, operates speculatively across an (un)natural paternal-fillialism that Derrida gleans from Freud’s interpretation of Moses as Jewish arch-patriarch. Keywords: Archive, Figuration, Materiality, Paternal-Fillialism, Writing Technologies